Preparation method of alcohol-soluble NiOx nano-particles as well as product and application of alcohol-soluble NiOx nano-particles
The synthesis of alcohol-soluble NiOx nanoparticles addresses the stability and compatibility issues of conventional NiOx in solar cells by using organic acids and amines, resulting in enhanced hole mobility and stability, making them a suitable alternative to Spiro-OMeTAD for solar cell applications.
Patent Information
- Application Number
- CN202411839034.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
Conventional NiOx nanoparticles are not stable in alcoholic solvents and limited in their application in inverted structure solar cells due to their water-based nature, which leads to instability and incompatibility with calcium titanate layers.
A method to synthesize alcohol-soluble NiOx nanoparticles through a process involving the use of organic acids, amines, and solvents, followed by ultrasonic treatment and ligand exchange to create a stable dispersion, allowing for the formation of a NiOx-based ink suitable for use as an air hole transport layer in solar cells.
The modified NiOx nanoparticles demonstrate improved hole mobility, stability, and compatibility with calcium titanate layers, outperforming traditional Spiro-OMeTAD in terms of stability and efficiency, enabling their use as a viable alternative in solar cells.
Smart Images

Figure CN119677303A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells and particularly relates to an alcohol-soluble NiO x Nanoparticle preparation method, products and applications. Background Art
[0002] With the development of science and technology, perovskite solar cells are becoming well-known as a new technology. The hole transport layer material used in formal devices is mainly sprio-OMeTAD, but due to its high price and short device life, it is gradually replaced by inorganic nano-NiOx. However, conventional NiOx is water-based, and water will destroy perovskite, making it less used in the upright structure.
[0003] In a perovskite solar cell with an upright structure, the layers from bottom to top are a transparent electrode layer, an electron transport layer, a light absorbing layer, a hole transport layer, and an electrode layer. The main advantage of this structure is that it is relatively simple, the preparation process cost is low, and light can first enter the electron transport layer after being incident on the transparent electrode. However, the hole transport material of the formal structure is mostly Spiro-OMeTAD, and in order to increase conductivity, additives such as Li salts and Co salts that are sensitive to water and oxygen are usually required. Although this achieves high efficiency, it also sacrifices the stability of the device.
[0004] In contrast, the hole transport layer materials of the trans structure are mostly inorganic metal oxides, such as NiO x , CuO, etc. These materials have better performance in terms of stability. x For example, it is prepared by sol-gel method, and its nanomaterial is made by calcining Ni(OH)2 at 280℃. But it should be noted that this NiO x The material can only be dispersed in water, but cannot be stably dispersed in alcohols, and cannot be made into alcohol-soluble spin-coating ink. Therefore, in practical applications, it is usually dispersed in water and then spin-coated on ITO or FTO. However, since the perovskite coating will dissociate when it encounters water, it is not possible to directly spin-coat NiO on the perovskite film. x This is not realistic, which correspondingly limits the application of NiOx in inverted perovskite solar cells. Summary of the invention
[0005] In view of the above technical problems, the present application provides an alcohol-soluble NiO x The invention discloses a method for preparing nanoparticles, a product thereof and an application thereof, so as to solve the problem that conventional NiOx cannot be stably dispersed in alcohols and has limited application in perovskite solar cells.
[0006] The technical solution adopted by the present invention is as follows:
[0007] Alcohol-soluble NiO x The method of producing nanoparticles comprises the following steps:
[0008] S1. Obtaining NiO x Nano powder;
[0009] S2. The organic acid, the organic amine, and the organic solvent are mixed in a certain proportion to form a first reaction solvent;
[0010] S3. NiO x The nanopowder is mixed with the first reaction solvent in a certain proportion, and the ligand reaction is carried out under ultrasonic dispersion for 0.1-24h to obtain oily NiO x Nanodispersions;
[0011] S4. The above oily NiO x The dispersion is centrifuged with a poor solvent, the precipitate is mixed with a multifunctional ligand, a certain volume of organic alcohol is added, and the ligand is exchanged by ultrasonication for 0.1-24h;
[0012] S5. The above reaction solution is precipitated with alkane to obtain alcohol-soluble NiO x Nanoparticles.
[0013] Furthermore, the organic acid described in S2 refers to a saturated or unsaturated organic acid with a carbon chain number of 4-22; the organic amine refers to a saturated or unsaturated organic amine with a carbon chain number of 4-22; and the organic solvent refers to a normal alkane with a carbon chain number of 6-13.
[0014] Furthermore, the nano NiO described in S1 x Powder refers to NiO with a particle size of 3-20nm x Nanoparticles.
[0015] Furthermore, the poor solvent described in S4 refers to one of ethanol, methanol, acetonitrile, acetone, and ethyl acetate.
[0016] Furthermore, the multifunctional ligand described in S4 is an organic compound having the following structure:
[0017]
[0018] Among them, A and D are para positions, wherein the A position is a carboxyl group (-COOH or -RCOOH); the D position is a hydroxyl group (-OH or -ROH), an amine group (-NH2 or -RNH2) or a thiol group (-SH or -RSH); wherein R represents an alkyl group or a hydrocarbon group, and B, C, E, and F are hydrogen, a halogen or an alkyl group.
[0019] Furthermore, the ultrasonic power in S4 is 200-1200W.
[0020] Alcohol-soluble NiO prepared by any of the above preparation methods x Nanoparticles, including NiO x Inorganic substances and NiO x The organic ligand on the surface of the inorganic substance has a weight of 3%-30% of the whole substance, and the band gap of the nanoparticle is 3.6-3.8 eV.
[0021] Further, in terms of the amount of substance, the NiO x The nanomaterial contains trivalent nickel and divalent nickel, and n(Ni(3+)) / n(Ni(2+)) is 0.2-2.
[0022] A conductive ink, comprising the alcohol-soluble NiO x , a first solvent and a second solvent, the first solvent is a straight-chain or branched saturated alcohol with a carbon chain number of 4-8, acting as the main solvent, and the second solvent is a membrane surface modifier, which is an alcohol ether with a carbon chain number of 4-8, an ester with a carbon chain number of 6-12, a low-viscosity polydimethylsiloxane, or pinene alcohol.
[0023] Furthermore, in terms of mass fraction, NiO x The content of the first solvent is 2%-10%, the content of the first solvent is 30%-40%, the content of the alcohol ether in the second solvent is 30%-50%, the content of the ester in the second solvent is 20%-30%, the content of the polydimethylsiloxane in the second solvent is 1%-5%, and the content of terpineol in the second solvent is 5%-20%.
[0024] The beneficial effects of the present invention are as follows:
[0025] The present invention uses ligand exchange to treat NiO x The nanoparticles are modified so that they can be dispersed in organic alcohols and are suitable for use as hole transport layer materials in an upright device structure. Since organic alcohols do not destroy the perovskite coating, the modified NiO x It has higher hole mobility (0.1-3.0cm) than sprio-OMeTAD 2 V -1 s -1 Compared to 1.0x10 -4 cm 2 V -1 s -1 ), while NiO x It is superior to sprio-OMeTAD in terms of UV resistance, thermal stability and weather resistance. x Nanomaterials can serve as alternatives to sprio-OMeTAD.
[0026] The present invention utilizes multifunctional aromatic carboxylic acid to react NiO x The strong coordination ability makes the prepared nanomaterials quite stable in alcohol ether inks. In addition, the use of alcohol, alcohol ether and ester solvents can provide suitable viscosity, leveling and volatility. The obtained conductive ink meets the requirements of spin coating, printing and spraying.
[0027] The conductive ink of the present invention has high stability and can be stored for a long time at room temperature without agglomeration, precipitation or stratification within one year. When spin coating is performed, a uniform NiO x Thin film; when printing, it will not block the nozzle and can suppress the coffee ring effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The alcohol-soluble NiO prepared by the present invention x TEM image of nanoparticles.
[0029] Figure 2 The alcohol-soluble NiO prepared by the present invention x XRD pattern of nanoparticles.
[0030] Figure 3 The alcohol-soluble NiO prepared by the present invention x UV-visible absorption graph of nanoparticles.
[0031] Figure 4 The alcohol-soluble NiO prepared by the present invention x Thermogravimetric analysis of nanoparticles. DETAILED DESCRIPTION
[0032] The present invention is described in detail below through specific embodiments.
[0033] The present invention provides a method for preparing alcohol-soluble NiO x The method of producing nanoparticles comprises the following steps:
[0034] S1. Obtaining NiO x Nano powder;
[0035] S2. The organic acid, the organic amine, and the organic solvent are mixed in a certain proportion to form a first reaction solvent;
[0036] S3. NiO x The nanopowder is mixed with the first reaction solvent in a certain proportion, and the ligand reaction is carried out under ultrasonic dispersion for 0.1-24h to obtain oily NiO x Nanodispersions.
[0037] S4. The above oily NiO xThe dispersion is centrifuged with a poor solvent, the precipitate is mixed with a multifunctional ligand, a certain volume of organic alcohol is added, and ultrasonic ligand exchange is performed for 0.1-24 hours.
[0038] S5. The above reaction solution is precipitated with alkane to obtain alcohol-soluble NiO x Nanoparticles.
[0039] NiO in S1 x Nanopowders can be prepared by various existing technologies or can be commercially available.
[0040] In this application, alcohol solubility refers to the ability to dissolve or disperse in straight-chain or branched organic alcohols with a carbon chain number of 5-20;
[0041] The present invention also provides an alcohol-soluble NiO x The nanoparticles have the following structure: NiO x Inorganic, NiO x The organic ligand on the surface. The band gap is calculated to be in the range of 3.6 eV-4.0 eV. The calculation method is well known to those skilled in the art, for example, it can be calculated by the Tauc Plot method, which will not be described here.
[0042] The surface of the nanoparticles carries some organic ligands, which are organic substances that conform to the following structure
[0043]
[0044] Among them, A and D are para positions, where A is a carboxyl group (-COOH or -RCOOH); D is a hydroxyl group (-OH or -ROH), an amine group (-NH2 or -RNH2) or a thiol group (-SH or -RSH); R represents an alkyl group or a hydrocarbon group, and B, C, E, and F are hydrogen, halogen or an alkyl group. Such as p-hydroxybenzoic acid, p-aminobenzoic acid, and p-mercaptobenzoic acid.
[0045] The weight of the ligands on the surface of the nanomaterial accounts for 3%-30% of the total weight. The hole mobility of the nanomaterial is 0.1-5.0cm 2 V -1 s -1 between.
[0046] In terms of the amount of substance, n(Ni(3+)) / n(Ni(2+)) in the nanomaterial of the present application is between 0.2-2.
[0047] The alcohol-soluble nanomaterials of the present invention are mainly used as hole transport materials in perovskite solar cells. Specifically, the nanomaterials can be deposited on the perovskite light-absorbing layer material by spin coating, spray coating, inkjet printing, etc.
[0048] According to another aspect of the present invention, there is provided an alcohol-soluble NiO x Conductive ink.
[0049] The conductive ink in this patent application includes alcohol-soluble NiO x and a first solvent and a second solvent. The first solvent is a straight-chain or branched saturated alcohol with a carbon chain number of 4-8, mainly serving as the main solvent; such as n-butanol and n-hexanol; the second solvent is a membrane surface modifier, such as alcohol ethers with a carbon chain number of 4-8, esters with a carbon chain number of 6-12, low-viscosity polydimethylsiloxane, and pinene alcohol. The main functions are to reduce the contact angle, increase the wettability of the membrane surface, leveling, eliminating foam, and inhibiting the coffee ring effect, such as diethylene glycol acetate, propylene glycol methyl ether acetate, etc.
[0050] The first solvent includes but is not limited to n-butanol, n-pentanol, tert-butanol, etc., preferably n-butanol;
[0051] The alcohol ethers in the second solvent include but are not limited to ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, preferably ethylene glycol monopropyl ether; the esters in the second solvent include but are not limited to propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, preferably propylene glycol methyl ether acetate; the polydimethylsiloxane in the second solvent includes but is not limited to polydimethylsiloxane with a viscosity of 100-10000 (mPa.s), preferably a viscosity of 300mPa.s. The terpineol in the second solvent includes but is not limited to α-terpineol, β-terpineol, γ-terpineol, or a mixture of two or more.
[0052] In this application, by controlling the content of different components, NiO x Conductive ink viscosity, conductivity, contact angle, surface tension, film surface flatness, defoaming, etc., so that it can meet the requirements of inkjet printing, spin coating, and scraping coating for ink, and obtain a relatively good film. x In conductive ink, NiO x The content of the first solvent is between 2% and 10%, the content of the first solvent is 30% to 40%, more preferably 30%, 35%, 40%; the content of the alcohol ether in the second solvent is 30% to 50%, more preferably 30%, 35%, 40%, 45%, 50%; the content of the ester in the second solvent is 20% to 30%, more preferably 20%, 25%, 30%; the content of the polydimethylsiloxane in the second solvent is 1% to 5%, more preferably 1%, 3%, 5%; the content of the terpineol in the second solvent is 5% to 20%, more preferably 5%, 10%, 15%, 20%.
[0053] NiO in this applicationx The conductivity of the conductive ink is between 1 and 100 μS / cm, which meets the needs of perovskite solar cells for hole transport materials.
[0054] Embodiment 1
[0055] S1. High temperature calcination to obtain NiO x Powder;
[0056] S2, mixing 1 ml of oleic acid, 5 ml of oleylamine, and 100 ml of n-heptane to form a first reaction solvent;
[0057] S3, 3g 5nmNiO x The powder was mixed with the first reaction solvent, and the ultrasonic power was 200W and the ultrasonic time was 4h to obtain oil-soluble nano NiO x Dispersion.
[0058] S4, the above oily NiO x The dispersion was centrifuged with isopropanol precipitation, 1.5 g of p-hydroxybenzoic acid was added to the precipitate, and then 100 ml of ethanol was added to perform ultrasonic ligand exchange for 0.5 h to obtain alcohol-soluble NiO. x Mother liquor.
[0059] S5, the reaction solution was centrifuged with n-heptane precipitation at a centrifugal speed of 5000 rpm to obtain alcohol-soluble NiO x Nanoparticles, the NiO x Can be dispersed in isopropyl alcohol.
[0060] test:
[0061] Take the above NiO x The perovskite solar cell is prepared by using an isopropanol dispersion according to the device spin coating method of the present invention.
[0062] Embodiment 2
[0063] S1. Preparation of NiO by high temperature thermal decomposition x Powder
[0064] S2. Mix 1mmol nickel chloride, 1.5mmol lithium stearate, 17ml oleic acid and 15ml oleylamine, and dissolve them transparently under vacuum and heating at 120℃ to obtain nickel oleate solution; raise the temperature of the above system to 300℃, add 2.5mmol n-octadecyl alcohol and 2ml oleylamine to the above high temperature system at 100℃, and keep the temperature for 3h to form NiO x Nanoparticles, with a particle size of about 5nm, are used to obtain oil-soluble NiO x Nano masterbatch;
[0065] S3, add 3 times the amount of ethanol to the above mother liquor, centrifuge and precipitate three times, dissolve with n-heptane, and obtain n-heptane dispersed oil-soluble NiO x Nanoparticles;
[0066] S4. Take the above 2g oily NiO x Nanopowder, and add 1.5g p-hydroxybenzoic acid, then add 100ml isopropanol, and ultrasonicate for 1h to perform ultrasonic ligand exchange to obtain alcohol-soluble NiO x Mother liquor.
[0067] S5. The mother liquor was centrifuged with 300 ml of n-heptane at a centrifugal speed of 5000 rpm to obtain alcohol-soluble NiO x Nanoparticles, the NiO x Can be dispersed in isopropyl alcohol.
[0068] Embodiment 3
[0069] Replacement of surface ligands
[0070] S1. Use commercially available NiO x Nano powder;
[0071] S2. 1 ml of lauric acid, 5 ml of oleylamine, and 100 ml of n-octane were mixed to form a first reaction solvent;
[0072] S3.3g 5nmNiO x The powder was mixed with the first reaction solvent, the ultrasonic power was 300W, and the ultrasonic time was 4h. The oil-soluble nano NiO x Dispersion.
[0073] S4. The above oily NiO x The dispersion was centrifuged with isopropanol precipitation, 2 g of p-aminobenzoic acid was added to the precipitate, and then 100 ml of isopropanol was added to perform ultrasonic ligand exchange, and ultrasonication was performed for 3 h to obtain alcohol-soluble NiO. x Mother liquor.
[0074] S5. The reaction solution was centrifuged with n-heptane precipitation at a centrifugal speed of 5000 rpm to obtain alcohol-soluble NiO x Nanoparticles, the NiO x Can be dispersed in isopropyl alcohol.
[0075] Embodiment 4
[0076] S1. High temperature calcination to obtain NiO x Powder;
[0077] S2. 1 ml of n-butyric acid, 3 ml of n-butylamine, and 100 ml of n-hexane were mixed to form a first reaction solvent;
[0078] S3.3g 5nmNiO x The powder was mixed with the first reaction solvent, the ultrasonic power was 300W, and the ultrasonic time was 4h. The oil-soluble nano NiO x Dispersion.
[0079] S4. The above oily NiO x The dispersion was centrifuged with isopropanol precipitation, 3 g of 2-chloro-4-hydroxybenzoic acid was added to the precipitate, and then 100 ml of isopropanol was added to perform ultrasonic ligand exchange, and ultrasonication was performed for 3 h to obtain alcohol-soluble NiO x Mother liquor.
[0080] S5. The reaction solution was centrifuged with n-heptane precipitation at a centrifugal speed of 5000 rpm to obtain alcohol-soluble NiO x Nanoparticles, the NiO x Can be dispersed in isopropyl alcohol.
[0081] Embodiment 5
[0082] This embodiment provides a conductive ink, wherein NiO x It is prepared by Example 1 of the present application, and the formula is as follows: NiO x The content of is 2.5%, the content of 1-hydroxyhexanethiol is 2%, the content of 1-hydroxyhexanoic acid is 1%, the content of n-butanol is 30%; the content of ethylene glycol monopropyl ether is 40%; the content of propylene glycol methyl ether acetate is 21%; the content of polydimethylsiloxane with a viscosity of 300mPa.s is 3.5%.
[0083] Using the above NiO x The ink can be used for inkjet printing and can be continuously printed for more than 5 hours. The ink conductivity is 20μS / cm, and the printing process is smooth, and a flat and uniform conductive film can be obtained.
[0084] Embodiment 6
[0085] This embodiment provides a conductive ink, wherein NiO x It is prepared by Example 2 of the present application, and the formula is as follows: NiO x The content of is 3%, the content of mercaptoethanol is 1.5%, the content of glycolic acid is 2%, the content of n-propanol is 35%, the content of ethylene glycol monobutyl ether is 30%, the content of propylene glycol methyl ether acetate is 25% and the content of terpineol is 3.5%.
[0086] Using the above NiO x The ink can be used for inkjet printing and can be printed continuously for more than 2 hours. The ink conductivity is 50μS / cm, and the printing process is smooth, and a flat and uniform conductive film can be obtained.
[0087] Embodiment 7
[0088] This embodiment provides a conductive ink, wherein NiO x It is prepared by Example 3 of the present application, and the formula is as follows: NiO x The content of is 2.5%, the content of 6-mercaptohexanol is 3%, the content of 1-hydroxyhexanoic acid is 3%, the content of n-butanol is 35%, the content of diethylene glycol monobutyl ether is 36%, the content of propylene glycol methyl ether acetate is 17% and the content of terpineol is 3.5%.
[0089] The conductive ink can be used for inkjet printing for more than 2.4 hours, the ink conductivity is 15μS / cm, and the printing process is smooth, and a flat and uniform conductive film can be obtained.
[0090] The spin coating method comprises the following steps: spin coating an isopropanol solution of zinc oxide on the ITO anode layer, and then annealing at 80°C for 10 min to form an electron transport layer; spin coating a perovskite solution on the electron transport layer as a carrier to form an absorption layer; spin coating the NiO in Example 1 on the absorption layer x The nanomaterial n-octane dispersion forms a hole transport layer after drying; finally, the Au cathode electrode layer is evaporated and encapsulated to form a perovskite solar cell device.
[0091] Inkjet printing method: In the above spin coating method, only the spin coating process is changed to inkjet printing into the perovskite light absorbing layer material, and the NiO is heated by gradient heating under high vacuum conditions. x Annealing of the layer material.
[0092] Comparative Example 1
[0093] S1. At 25°C, 0.3 mol of nickel nitrate and 1 L of water were mixed to obtain a first reaction system;
[0094] S2. 0.6 mol of NaOH was added to the first reaction system, and the reaction was continued for 2 h to obtain a Ni(OH)2 sol dispersion system;
[0095] S3. The Ni(OH)2 sol dispersion is centrifuged and washed twice with water until the nitrate ions are completely eluted;
[0096] S4. S4 was calcined at 280℃ for 1h to obtain black NiO x calcined body;
[0097] S5. NiO x The nanopowder was ultrasonicated for 1 h under an ultrasonic probe to obtain NiO x Nanoparticles in water.
[0098] Table 1: Comparison of device performance results in various embodiments
[0099]
[0100]
[0101] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. Alcohol-soluble NiO x The method of nanoparticles is characterized in that The following steps are involved: S1. Obtaining NiO x Nano powder; S2. The organic acid, the organic amine, and the organic solvent are mixed in a certain proportion to form a first reaction solvent; S3. NiO x The nanopowder is mixed with the first reaction solvent in a certain proportion, and the ligand reaction is carried out under ultrasonic dispersion for 0.1-24h to obtain oily NiO x Nanodispersions; S4. The above oily NiO x The dispersion is centrifuged with a poor solvent, the precipitate is mixed with a multifunctional ligand, a certain volume of organic alcohol is added, and the ligand is exchanged by ultrasonication for 0.1-24h; S5. The above reaction solution is precipitated with alkane to obtain alcohol-soluble NiO x Nanoparticles.
2. Alcohol-soluble NiO according to claim 1 x The method of nanoparticles is characterized by: The organic acid described in S2 refers to saturated or unsaturated organic acids with a carbon chain number of 4-22; the organic amine refers to saturated or unsaturated organic amines with a carbon chain number of 4-22; and the organic solvent refers to normal alkanes with a carbon chain number of 6-13.
3. Alcohol-soluble NiO according to claim 1 x The method of nanoparticles is characterized by: The nano-NiO described in S1 x Powder refers to NiO with a particle size of 3-20nm x Nanoparticles.
4. Alcohol-soluble NiO according to claim 1 x The method of nanoparticles is characterized by: The poor solvent described in S4 is one of ethanol, methanol, acetonitrile, acetone and ethyl acetate.
5. Alcohol-soluble NiO according to claim 1 x The method of nanoparticles is characterized by: The multifunctional ligand described in S4 is an organic compound that conforms to the following structure Among them, A and D are para positions, wherein the A position is a carboxyl group (-COOH or -RCOOH); the D position is a hydroxyl group (-OH or -ROH), an amine group (-NH2 or -RNH2) or a thiol group (-SH or -RSH); wherein R represents an alkyl group or a hydrocarbon group, and B, C, E, and F are hydrogen, a halogen or an alkyl group.
6. Alcohol-soluble NiO according to claim 1 x The method of nanoparticles is characterized by: The ultrasonic power in S4 is 200-1200W.
7. Alcohol-soluble NiO prepared by any one of the preparation methods of claims 1 to 6 x Nanoparticles, including NiO x Inorganic substances and NiO x The organic ligand on the surface of the inorganic substance has a weight of 3%-30% of the whole substance, and the band gap of the nanoparticle is 3.6-3.8 eV.
8. Alcohol-soluble NiO according to claim 7 x Nanoparticles, characterized in that: In terms of the amount of substance, the NiO x The nanomaterial contains trivalent nickel and divalent nickel, and n(Ni(3+)) / n(Ni(2+)) is 0.2-2.
9. A conductive ink comprising the alcohol-soluble NiO as claimed in claim 7 x , a first solvent and a second solvent, the first solvent is a straight-chain or branched saturated alcohol with a carbon chain number of 4-8, acting as the main solvent, and the second solvent is a membrane surface modifier, which is an alcohol ether with a carbon chain number of 4-8, an ester with a carbon chain number of 6-12, a low-viscosity polydimethylsiloxane, or pinene alcohol.
10. The conductive ink according to claim 9, characterized in that: In terms of mass fraction, NiO in conductive ink x The content of the first solvent is 2%-10%, the content of the first solvent is 30%-40%, the content of the alcohol ether in the second solvent is 30%-50%, the content of the ester in the second solvent is 20%-30%, the content of the polydimethylsiloxane in the second solvent is 1%-5%, and the content of terpineol in the second solvent is 5%-20%.